(untitled) (Research, Society and Development, 2020)
The aim of this study was to assess the quality of life and burden of caregivers of adolescents aged 10 to 19 years with autism spectrum disorder, enrolled in state and private public schools in Recife. Cross-sectional study with a sample of 57 caregivers (44 in the state public school and 13 in the private one). Data were collected using the instruments: The World Health Organization for Quality of Life (short version) in the assessment of quality of life and the Zarit Burden Interview Scale to assess the burden. The statistical program Statistical Package for Social Science, version 17.0, was used for analysis, with a significance level of p <0.05. The sample, mostly were mothers (89.5%) whose main occupation was that of the home (71.9%), with a monthly family income of up to 2 minimum wages (70.2%). They had a lower perception of global quality of life in the environmental domain (40.95), followed by the psychological (47.22), physical (51.44) and social (53.95) domains. The quality of life in the state public school system was assessed and the highest average was obtained for the social domain (56.25) and the lowest for the environmental domain (39.42). In the private network, the highest average was the physical domain (49.45) and the lowest for the environmental and social domains (identical in 46.15). The greatest global burden on caregivers was the state public school system (45.18). The quality of life and burden of caregivers is low and there is a need for state subsidies to improve the perception of quality of life and burden in the state public network.